THE EFFECT OF LEADERSHIP STYLE AND SUPERVISION ON EMPLOYEE PERFORMANCE - Andy Hakim; Joli Afriany (SEAN Institute, 2023)
This study aims to determine the effect of leadership style, supervision on employee performance in The data sources used are data obtained from questionnaire records and documentation. Consistently, each variation (X) has a penalty for the employee's work. Leaders directly involved in the work have personal experience with how employees are paid. The sampling technique used a proportional stratified random sampling method in which 150 respondents were taken as samples. The analytical technique combines statistical analysis with regression, correlation, determination, and hypothesis testing. The result of this research is that the gay leadership variable is an average score of around 0.694 with good criteria. The average score of 0.105 with good criteria is used for monitoring variables.